The Importance of Kinetics and Redox in the Biogeochemical Cycling of Iron in the Surface Ocean - Croot, Peter L.; Heller, Maija I. (Frontiers in Microbiology, 2012)
It is now well established that Iron (Fe) is a limiting element in many regions of the open ocean. Our current understanding of the key processes which control iron distribution in the open ocean have been largely based on thermodynamic measurements performed under the assumption of equilibrium conditions. Using this equilibrium approach, researchers have been able to detect and quantify organic complexing ligands in seawater and examine their role in increasing the overall solubility of iron. Our current knowledge about iron bioavailability to phytoplankton and bacteria is also based heavily on carefully controlled laboratory studies where it is assumed the chemical species are in equilibrium in line with the free ion association model (FIAM) and/or its successor the biotic ligand model (BLM). Similarly most field work on Fe biogeochemistry generally consists of a single profile which is in essence a ‘snap-shot’ in time of the system under investigation. However it is well known that the surface ocean is an extremely dynamic environment and it is unlikely if thermodynamic equilibrium between all the iron species present is ever truly achieved. In sunlit waters this is mostly due to the daily passage of the sun across the sky leading to photoredox processes which alter Fe speciation by cycling between redox states and between inorganic and organic species. Episodic deposition events, are also important perturbations to iron cycling as they bring new iron to the system altering the equilibrium between species and phases. Over the last 20 years the mesoscale iron enrichment experiments (e.g. IronEx I /II, SOIREE, EisenEx, SOFeX, EIFeX, SAGE, SEEDS and SERIES I /II) and the FeCycle (I/II) experiments have provided the first insights into processes altering iron speciation and distribution which occur over temporal scales of days to weeks. Here we utilize new field data collected in the open ocean on the redox and complexation kinetics of iron in the euphotic zone.